2013
DOI: 10.1016/j.archoralbio.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compressive force on human osteoblast-like cells and bone remodelling: An in vitro study

Abstract: The results suggest that initial application of CF on HOBs can simultaneously affect expression of markers related to both osteogenesis and osteoclastogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 162 publications
1
51
0
Order By: Relevance
“…Briefly, confluent cells were subjected to a static compressive force by placing a glass cylinder with lead weights onto the cells of a 6-well plate. The intensity of the force was controlled at 294 Pa by numbers of lead granules placed in the cylinder, because force of compression in vivo is assumed between 2.0 g/cm 2 (196 Pa) to 4.0 g/cm 2 (392 Pa) (10,11). A cell area in contact with the cylinder was marked beforehand on the bottom of the wells.…”
Section: Application Of Compressive Forcementioning
confidence: 99%
“…Briefly, confluent cells were subjected to a static compressive force by placing a glass cylinder with lead weights onto the cells of a 6-well plate. The intensity of the force was controlled at 294 Pa by numbers of lead granules placed in the cylinder, because force of compression in vivo is assumed between 2.0 g/cm 2 (196 Pa) to 4.0 g/cm 2 (392 Pa) (10,11). A cell area in contact with the cylinder was marked beforehand on the bottom of the wells.…”
Section: Application Of Compressive Forcementioning
confidence: 99%
“…In studies that reported contradictory results using similar loading methods, magnitude was a major difference. A previous study reported that a compressive stress of 1.0 g/cm 2 is optimal for osteoblastic differentiation13, but another study observed enhanced osteoblastic differentiation when compression was raised from 2.0 g/cm 2 to 4.0 g/cm 2  11. Therefore, magnitude may be one of the parameters that determine the role of mechanical stress in bone remodeling.…”
mentioning
confidence: 99%
“…Unfortunately, in vitro studies showed contradictory results on the responses under compressive stress: inhibited/enhanced osteoblastic differentiation and inhibited/enhanced osteoblast-regulated osteoclastic differentiation have both been reported9101112. In studies that reported contradictory results using similar loading methods, magnitude was a major difference.…”
mentioning
confidence: 99%
“…It was demonstrated that OPN has a role in cell adhesion, migration, cell survival and bone remodelling [18][19][20]. Research in animal models has indicated that OPN deficiency alters the functionality of multiple cell types, resulting in delayed early vascularization, altered matrix organization and late bone remodelling [21].…”
Section: Discussionmentioning
confidence: 99%